Role of a Ferredoxin Gene Cotranscribed with the nifHDK Operon in N(2) Fixation and Nitrogenase “Switch-Off” of Azoarcus sp. Strain BH72 - Egener, Tanja (American Society for Microbiology, 2001)
The endophytic diazotroph Azoarcus sp. strain BH72 is capable of infecting rice roots and of expressing the nitrogenase (nif) genes there. In order to study the genetic background for nitrogen fixation in strain BH72, the structural genes of nitrogenase (nifHDK) were cloned and sequenced. The sequence analysis revealed an unusual gene organization: downstream of nifHDK, a ferredoxin gene (fdxN; 59% amino acid sequence identity to R. capsulatus FdxN) and open reading frames showing 52 and 36% amino acid sequence identity to nifY of Pseudomonas stutzeri A15 and ORF1 of Azotobacter vinelandii were located. Northern blot analysis, reverse transcriptase PCR and primer extension analysis revealed that these six genes are located on one transcript transcribed from a ς(54)-type promoter. Shorter transcripts sequentially missing genes of the 3′ part of the full-length mRNA were more abundantly detected. Mutational analyses suggested that FdxN is an important but not the essential electron donor for dinitrogenase reductase. An in-frame deletion of fdxN resulted in reduced growth rates (59% ± 9%) and nitrogenase activities (81%) in nitrogen-fixing pure cultures in comparison to the wild type. Nitrogenase activity was fully complemented in an fdxN mutant which carried a nifH promoter-driven fdxN gene in trans. Also, in coculture with the ascomycete Acremonium alternatum, where strain BH72 develops intracytoplasmic membrane stacks, the nitrogenase activity in the fdxN deletion mutant was decreased to 56% of the wild-type level. Surprisingly, the fdxN deletion also had an effect on the rapid “switch-off” of nitrogenase activity in response to ammonium. Wild-type strain BH72 and the deletion mutant complemented with fdxN in trans showed a rapid reversible inactivation of acetylene reduction, while the deletion mutant did not cease to reduce acetylene. In concordance with the hypothesis that changes in the redox state of NifH or electron flux towards nitrogenase may be involved in the mechanism of physiological nitrogenase switch-off, our results suggest that the ferredoxin may be a component involved in this process.